The Status of Convention on Biological Diversity (CBD) Leading to Cop - 8 - Tripathi, Sandeep; Srivastava, Anita (Indian Forester, 2007)
The Convention on Biological Diversity (CBD) provides a frame work for sustainable management and conservation of India's natural resources. Till now, 188 countries including India and the European Community have become Parties to the Convention. Since 1992, eight Conference of the Parties (COP) meetings have been organized under CBD. The legislation on bio-diversity in the country is on the anvil. The relevant provisions of Convention on Biological Diversity regarding conservation are therefore of utmost importance, and the proposed National Biodiversity Action Plan must be able to fulfill them. Despite several enactments, rules and regulations, India has decided to come forward with the Biological Diversity Bill, 2002 which shows its concern about bio-piracy; biodiversity and fair and equitable-benefit-sharing. The COP meetings discuss or share ideas on practices and policies for the conservation and sustainable use of biodiversity. Promotion of transboundary cooperation, and involvement of indigenous peoples and local communities in ecosystem management are the other issues that are discussed. The Conference of the Parties has launched a number of thematic programmes covering the biodiversity of inland waters, forests, marine and coastal areas, drylands and agricultural lands. Cross-cutting issues such as the control of alien invasive species, strengthening the capacity of member states are also deliberated upon to evolve the best practices towards sustainable use of biodiversity.